ASUHAN KEPERAWATAN PADA TN. R DENGAN HIPERTENSI DI PANTI SOSIAL TRESNA WERDHA BUDI MULIA 1 KECAMATAN CIPAYUNG KOTA JAKARTA TIMUR - Annisa Kartika Maharani (2023)
Background: Hypertension is a condition in which the measurement results of systolic blood pressure > 130 mmHg and diastolic blood pressure > 90 mmHg. Hypertension is a serious health problem and includes a type of non-communicable disease. Hypertension is the leading cause of death globally due to non-communicable diseases. This research was conducted to obtain a real picture of the application of nursing care to Mr. R with hypertension at the Tresna Wherda Budi Mulia social institution 1. The research design used was a case study in the form of nursing care with an approach through assessment, determining diagnoses, planning interventions, implementing and carrying out nursing evaluations. Results: The main nursing problem in cases is acute pain related to physiological injury agents and progressive muscle relaxation therapy is given to reduce pain scale and lower blood pressure. After being given progressive muscle relaxation therapy the patient experienced a decrease in pain scale on the first day a scale of 4 (1-10) and on the third day a scale of 0 (1-10) and also experienced a decrease in blood pressure on the first day to 169/123 mmHg and on the third day to 133/82 mm Hg. Conclusion: Application of nursing care to Mr. R with hypertension achieved the expected results because of a decrease in the headache scale and also a decrease in blood pressure.